2014
DOI: 10.1111/are.12592
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of diatoms to bioflocs lipid content and the performance of juvenileLitopenaeus vannamei(Boone, 1931) in a BFT culture system

Abstract: This study aimed to evaluate the contribution of three diatom species on the lipid content of bioflocs, their permanence on the bioflocs and influence on the growth performance of juvenile shrimps. Juveniles of Litopenaeus vannamei were reared (30 days; three replicates per treatment) in biofloc systems inoculated with diatoms Amphora coffeaeformis (A), Cylindrotheca closterium (C), Conticribra weissflogii (W), or biofloc only (BF, chlorophycean rich). Water quality parameters were monitored daily and the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…In this study, due to daily alkalinity correction, no decrease in pH levels was observed during the experimental period. In relation to P-orthophosphate, the addition of the diatoms did not reduce this nutrient, similar to what was observed with Navicula sp., Amphora coffeaeformis, Cylindrotheca closterium and Conticribra weissflogii addition in BFT systems Martins, Odebrecht, Jensen, D'Oca, & Wasielesky, 2016). In relation to P-orthophosphate, the addition of the diatoms did not reduce this nutrient, similar to what was observed with Navicula sp., Amphora coffeaeformis, Cylindrotheca closterium and Conticribra weissflogii addition in BFT systems Martins, Odebrecht, Jensen, D'Oca, & Wasielesky, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…In this study, due to daily alkalinity correction, no decrease in pH levels was observed during the experimental period. In relation to P-orthophosphate, the addition of the diatoms did not reduce this nutrient, similar to what was observed with Navicula sp., Amphora coffeaeformis, Cylindrotheca closterium and Conticribra weissflogii addition in BFT systems Martins, Odebrecht, Jensen, D'Oca, & Wasielesky, 2016). In relation to P-orthophosphate, the addition of the diatoms did not reduce this nutrient, similar to what was observed with Navicula sp., Amphora coffeaeformis, Cylindrotheca closterium and Conticribra weissflogii addition in BFT systems Martins, Odebrecht, Jensen, D'Oca, & Wasielesky, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…Campaña‐Torres, Martínez‐Córdova, Villarreal‐Colmenares, Hernández‐López, Ezquerra‐Brauer and Cortés‐Jacinto () and Martins et al . () observed no influence on orthophosphate levels with plankton addition. In our study, a lower C:N ration was used (12:1) thus favouring a higher light penetration and microalgae uptake.…”
Section: Discussionmentioning
confidence: 85%
“…; Martins et al . ). The microbial community present in biofloc systems significantly improves weight gain and FCR of shrimp, thus potentially reducing the feed cost associated with shrimp production (Avnimelech ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Martins et al . () pointed out that the microalgae diatoms developed in the biofloc can provide essential fatty acids (especially EPA and linoleic) to shrimp.…”
Section: Innovative Sourcesmentioning
confidence: 97%